(untitled) (Research, Society and Development, 2023)
Psychrophilic aerobic bacteria have an optimal growth temperature of 15°C. These are related to the deterioration of processed meat and dairy products preserved at low temperatures. Thus, this study aimed to evaluate the microbiological parameters of psychrophilic bacteria and molds and yeasts in cheeses and hams sold in the municipality of Imperatriz - MA. Microbiological analysis was carried out on samples of coalho cheese and cooked ham, counting psychrophilic bacteria on plates (spread-plate method) and counting molds and yeasts. Cooked ham samples showed an average psychrophilic bacteria count of 1.4x104 CFU/g and an average mold and yeast count of 1.7x104 CFU/g of food. Regarding the coalho cheese samples, an average of 3.6x10⁴ CFU/g of psychrophilic bacteria count and 1.3x10² CFU/g for mold and yeast count was obtained. The results obtained indicate that the samples were in precarious conditions of hygiene and storage. It is also important to emphasize that contamination by these microorganisms results in sensory alterations in foods and a decrease in shelf life.